Understanding the Primary Liquid Products of Cellulose Hydrolysis in Hot-Compressed Water at Various Reaction Temperatures - Yu, Yun; Wu, Hongwei (American Chemical Society, 2010)
Knowledge on the primary liquid products is essential to understanding the primary hydrolysis reactions that take place on the surface of microcrystalline cellulose particles during hydrolysis in hot-compressed water (HCW). This study reports the experimental results on the primary liquid products from the hydrolysis of cellulose using a semicontinuous reactor system under optimized reaction conditions. The primary liquid products contain glucose oligomers and their derivatives with a wide range of degrees of polymerization (DPs), from 1 to a maximal DP, which increases with temperature from 23 at 230 °C, to 25 at 250 °C, then to 28 at 270 °C. Temperature also has a significant influence on the distribution of glucose oligomers in the primary liquid products. The results suggest that the hydrolysis reactions proceed on the surface of reacting cellulose particles via the cleavage of the accessible glycosidic bonds within the structure of microcrystalline cellulose in a manner with randomness. Thermal degradation reactions seem also to take place in a similar manner but to a much lesser extent. The randomness of these reactions is temperature-dependent and likely related to the change in the accessibility of glycosidic bonds, as a result of the cleavage of hydrogen bonds in the structure of microcrystalline cellulose. The hydrolysis reactions also seem to be accompanied by other parallel reactions (e.g., cross-linking reactions), which may affect the primary liquid products as well, particularly at high temperatures. The post-hydrolysis of primary liquid products has a high glucose yield of ~80% on a carbon basis, suggesting that HCW treatment may become an effective pretreatment method to break down long-chain microcrystalline cellulose into short-chain glucose oligomers for bioethanol production.